The Satisfaction of the Fishermen in the South China Sea With the Summer Fishing Moratorium System and Its Influencing Factors - Zhang, Lei; Wu, Qiaer; Zhou, Yanbo; Ma, Shengwei (Frontiers in Environmental Science, 2022)
ABSTRACT This study investigated the satisfaction of fishermen with the summer fishing moratorium system in the three provinces of the South China Sea through questionnaire survey, and explore the degree of its influencing factors. A multi-stage random sampling method was used to issue questionnaires to fishermen involved in summer fishing moratorium. A total of 258 valid questionnaires were collected, and the factor analysis method was used for principal component analysis in SPSS 23.0 software. The results showed that the variance contribution rate of the first five factors reached 61.859%, and the 11 influencing factors could be summarized as five factors that had a greater impact on the satisfaction of the summer fishing moratorium, such as “economic income during fishing moratorium (16.396)”, “illegal fishing boat (12.095)”, “fishing moratorium time（12.012）”, “law enforcement credibility (11.853)”, “summer fishing moratorium effect (9.503)”. According to the factor score calculation, the fishermen's satisfaction with the fishing moratorium was F=3.53, and the overall satisfaction was relatively high. This study reveals the satisfaction degree of the fishermen in the South China Sea with the summer fishing moratorium system and its influencing factors, which can provide a basis for improving the summer fishing moratorium system and ensuring the lives of fishermen.